Challenges of information systems innovation in developing country contexts: an inquiry into the adoption of institutional repositories in Nigerian universities - Utulu, Samuel Chiedu (Department of Information Systems, 2019)
Empirical observation persistently shows that information systems (IS) innovation is always hampered by different challenges. The number of failures and incomplete IS innovation reported across the globe, particularly in developing countries justifies this. Using the example of institutional repository (IR), an IS used to promote open access to scientific knowledge produced by universities, this study proposes actionable remedies to challenges of IS innovation in universities in developing countries. This study focuses on IR because little of it exists in universities in developing countries despite the fact that it is a cost effective way for universities to distribute scientific knowledge. IR has also not been a major focus of IS researchers despite its importance in the contemporary global academic landscape. The study therefore aims to develop explanation and solutions to barriers to IR innovation in universities in developing countries. The qualitative interpretive research philosophy was adopted together with the case study research method to conduct three empirical studies. Inductive research approach and unstructured qualitative data collection techniques were also adopted. Study 1 was carried out to assess IR innovation barrier factors at the institutional level. It reveals how globalization trends, transformation of universities and conditions of university libraries constitute IR innovation factors at institutional level. Study 2 was carried out to assess IR innovation barrier factors at the organizational level. It shows how institutional logics, adherence by universities to traditional university management orientations and paradox barrier factors constitute IR innovation factors at the organizational level. Study 3 identifies factors that influence effective tacit knowledge management at the individual level. The factors are namely, privileged information and experiences, mental reflection, planned interactions and dialogues and sustained real-time enactment of IR innovation. The three studies provide a set of theoretical and practical insights that contribute to the IS discipline, IS in developing countries and IR innovation. The contributions show how institutional, organizational and individual level factors influence IR innovation. The study reaches its goal of providing understanding and resolution to IS innovation barriers in universities in developing countries and in contexts that have similar socio-technical characteristics.